Professional Teachers and Bright Students in the View of the Qur'an and Prophetic Education - Yahya Muhdiana Fauzin; Muthoifin; Muchammad Taufiq Affandi (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study is to find out the concept of teacher and student contained in surah al-Kahf verses 65-78 perspective of tafsir at-Thabari and tafsir al-Maraghi. then know the similarities and differences as well as the implications of the concepts of teacher and student in surah al-Kahf verses 65-78 in today's life. The benefits are to increase scientific insight in the field of education and reading materials. This research uses a qualitative approach. With the type of research used is library research, the method used in this study is muqaran, which compares tafsir at-Thabari and tafsir al-Maraghi in surah al-kahfi verses 65-78, with this comparison will appear similarities and differences. Then the result of the explanation of this two mufassir, the author mentions points that are the concept of teachers, namely murabbi, mu'allim, murshid, muaddib, and mudarris with aspects of the criteria of dedication tawadhu', zuhud and wara', firm and responsible, patient, and forgiving. While the concept of talib students and students has aspects of dedication criteria, namely: intention because of Allah, respect for manners, tawadhu', patience, steadfastness, obedience, and obedience. The similarity between the interpretation of at-Thabari and al-Maraghi is that both use the tahlili method with the bil ma'tsur approach only. While al-Maraghi in his interpretation uses the tahlili method, the bil ma'tsur approach is combined with bil ra'yi and patterned after al-adabi al-ijtima'iy. The implications in contemporary life on the five teacher concepts must run as a whole and complement each other to become competent teachers according to the community environment. Students must realize themselves as students or talib so that the learning process goes well.